Customer Relationship Management Practices as Determinants of Business Performance: A Systematic Literature Review - Lasola, Mary Joan B. (Future Science / FSH-PH Publications, 2025)
Customer relationship management, or CRM, has become a crucial component that affects how well businesses, particularly accounting outsourcing organizations, function globally. This study addresses the gap in literature regarding the influence of Customer Relationship Management (CRM) practices on the business performance of accounting outsourcing firms. This study aims to have a systematic literature review on Customer Relationship Management practices as determinants of Business Performance. Moreover, this study employed a systematic literature review to examine the CRM practice and Business Performance of accounting outsourcing firms. This study draws on 10 studies published within year 2020 to 2025. The literature review highlights the need to further explore the connection between CRM practices and the commercial performance of accounting outsourcing companies. To give practitioners useful information, the study looks at the relationship between CRM dimensions such as customer engagement, client retention, and service customization and financial and non-financial performance. In conclusion, the main findings reveal that CRM dimensions are critical to improving both financial and non-financial performance, particularly for small and medium-sized enterprises (SMEs). The study's implications suggest that accounting outsourcing firms can enhance competitiveness by integrating advanced CRM strategies and leveraging data-driven insights to build stronger client relationships and respond more effectively to evolving client needs.